Wyzwania w nauczaniu na odległość i w wirtualnej klasie – zastosowanie programu Adobe Acrobat Connect Pro - MEDIC, Branko (Journal of Education, Technology and Computer Science, 2011)
This paper is my humble contribution to the advancement of Distance Tutoringand e-Learning in Serbia where technical requirements have made it possiblefor educators to develop their skills in tutoring online. The paper will examinesome advantages and disadvantages of the leading industry platform AdobeConnect Pro Meeting and my personal experience in engaging students to developtheir skills in presenting content online to other students of the world. Thepaper will also show that delivering classes online to the students of the world isa great challenge even for those lecturers who are fluent in English and are confidentin their teaching approach and classroom management skills in the physicalclassroom. The experience of Distance Tutoring is certainly rewarding andthe students have embraced the new technologies most enthusiastically becauseit gives them an opportunity to market their knowledge and skills even beforethey graduate from vocational schools or colleges.